2019
DOI: 10.31234/osf.io/x6ujz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Captivated by thought: “sticky” thinking leaves traces of perceptual decoupling in task-evoked pupil size

Abstract: Throughout the day, we may sometimes catch ourselves in patterns of thought that we experience as rigid and difficult to disengage from. Such “sticky” thinking can be highly disruptive to ongoing tasks, and when it turns into rumination constitutes a vulnerability for mental disorders such as depression and anxiety. The main goal of the present study was to explore the stickiness dimension of thought, by investigating how stickiness was reflected in task performance, and pupil size. To measure spontaneous thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…They reported that "stickiness" had substantial effects on the performance of the participants in the task and indicated that increase in self reported "stickiness" instances may be related to tendencies of depression. Level of "stickiness" has also been shown to be associated with pupil size 13 . In this study, we explore if EEG signals can capture this subtle state and allow more reliable differentiation, as pupil size is sensitive to arousal in general whereas EEG has been related to a variety of functions including attention, memory and emotion.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that "stickiness" had substantial effects on the performance of the participants in the task and indicated that increase in self reported "stickiness" instances may be related to tendencies of depression. Level of "stickiness" has also been shown to be associated with pupil size 13 . In this study, we explore if EEG signals can capture this subtle state and allow more reliable differentiation, as pupil size is sensitive to arousal in general whereas EEG has been related to a variety of functions including attention, memory and emotion.…”
Section: Introductionmentioning
confidence: 99%